(untitled) (De Musica, 2021)
In the era in which the web is fully demonstrating its archival potential, more and more composers make use of sound, melody and computer library repositories. It is a clear trend in popular music, which is increasingly being extended also to ‘academic’ composition: today authors can access and contribute to a vast array of audio materials, of procedures and languages, where historicity and innovation coexist in an eternal present. At first glance it may seem a revolution. However, a closer look reveals ancient roots in the history of music that audio reproduction has made only more evident: the fixation of music on tape, at first, has led some composers (e.g. Bruno Maderna) to create sound libraries to be reused in different works, thus blurring the borders of the Opera; later on, the dematerialization and atomization of procedures in IT have pushed towards a philosophy of sharing (e.g. libraries for Computer Assisted Composition systems) – exalted today by the capillarity of the lightning-fast web distribution – raising deep questions about the concept of author itself. Moving further backwards, to the re-uses in Rossini and Mozart, or to the anonymous formulas in Gregorian chant, could we not find the recurrence of a quest for that world of «myriad strains that once shall sound», where the composer can stretch forth a hand for a musical idea, so wonderfully glimpsed by Busoni in his Sketch for a New Esthetic of Music?